Long Lasting Antibodies From Convalescent Pertussis Patients Induce ROS Production and Bacterial Killing by Human Neutrophils - Kroes, Michiel M.; van Vliet, Lars C.; Jacobi, Ronald H. J.; Kuipers, Betsy; Pieren, Daan K. J.; Miranda-Bedate, Alberto; van Els, Cécile A. C. M.; Pinelli, Elena (Frontiers in Cellular and Infection Microbiology, 2022)
Pertussis is a respiratory infection caused by the Gram-negative bacterium Bordetella pertussis. Despite high vaccination coverage this disease remains a public health concern worldwide. A better understanding of the protective immune responses to B. pertussis is required for the development of improved vaccines. The aim of this study was to determine the production of reactive oxygen species (ROS) by human neutrophils in response to B. pertussis and to determine the contribution of opsonizing antibodies from convalescent pertussis patients in this response. The serum samples from convalescent patients were taken at <3, 9, 18 and 36 months after diagnosis of pertussis. Also included were sera from healthy age-matched controls. We show that neutrophils produced high levels of ROS in response to opsonized, compared to non-opsonized, B. pertussis and that this effect was independent of the time the convalescent serum samples were taken. This indicates the presence of functional opsonizing antibodies up to 3 years after B. pertussis infection. While opsonization of B. pertussis with serum samples from uninfected controls also induced ROS production, sera from infected individuals induced significantly higher ROS levels. Spearman correlations analysis showed that IgG antibodies targeting fimbriae3 followed by pertactin, and BrkA correlate with ROS production. Additionally, we observed that neutrophils killed opsonized B. pertussis in a ROS-dependent manner. Searching for other antigen-specific antibodies from convalescent pertussis patients involved in ROS production by neutrophils may assist in the identification of novel antigens to improve the current pertussis vaccines.